Ancient Households on the North Coast of Peru - Cutright, Robyn E.; Pacifico, David; Johnson, Ilana (Book collections on Project MUSE., 2021)
"Not limited to one time period or civilization, provides insight into the development of complex, urban, and state-level society in the region, showing how observed domestic patterns inform a new archaeological perspective on general processes in domestic life in and beyond Andean prehistory."--